PEMBUATAN DAN IMPLEMENTASI SISTEM INFORMASI PENDUKUNG KEPUTUSAN DALAM PENENTUAN DOSEN PEMBIMBING TUGAS AKHIR DI POLITEKNIK NEGERI BALIKPAPAN - Dwi Lesmideyarti; Ihsan Ihsan; Armin Armin (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
As we all know, technology is currently developing very rapidly. Almost all fields of work have used technology related to computer technology, including decision support systems. Based on observations that have been made at Poltekba, especially the Department of Electrical Engineering, the mentoring process is still constrained by the lack of appropriateness in the field of expertise between students and their supervisors. Where this can cause difficulty in consultation between supervisors and students regarding the work on the Final Project to be done. This study offers the implementation of a system that can be used to select prospective Final Project supervisors according to the student's field of expertise, namely designing a Decision Support System to determine the right prospective supervisor. Based on previous research in 2021, a suitable design and system for the selection of the final project supervisor is a Decision Support System with the Profile Matching method. Profile Matching assumes that there is an ideal predictor value that must be achieved, not a minimum value that must be passed, so this method is very suitable if used for the matching process. The results of this final project indicate that the system created has succeeded in choosing a supervisor who is in accordance with the theme taken by the students, with an accuracy rate of 100% between the suitability of manual calculations and system calculations. This is evidenced by comparing the manual calculation process with the system that has been created, where the ranking results show the same results.Keywords: Criteria, decision making, profile matching method